2022
DOI: 10.3390/ijms231911341
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Type 2 Receptor Activation Regulates Blue Light Exposure-Induced Mouse Corneal Epithelial Damage by Modulating Impaired Autophagy and Apoptosis

Abstract: The MT1/2 receptors, members of the melatonin receptor, belong to G protein-coupled receptors and mainly regulate circadian rhythms and sleep in the brain. Previous studies have shown that in many other cells and tissues, such as HEK293T cells and the retina, MT1/2 receptors can be involved in mitochondrial homeostasis, antioxidant, and anti-inflammatory responses. In our study, we aimed to investigate the effects of blue light (BL) exposure on the expression of melatonin and its receptors in the mouse cornea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In this study, we found that blue light-induced suppression of PI3K/AKT signaling can increase accumulation of ROS in hCECs in vitro, indicating the vital role of PI3K/AKT signaling in ROS metabolism in corneal epithelium under the blue light exposure. Actually, many previous researches showed that blue light exposure can induce apoptosis of CECs in vivo and/or in vitro (2,24). And dysregulation of ROS stress is widely considered as an important mechanism of corneal epithelial damage caused by excessive blue light exposure(25-27).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that blue light-induced suppression of PI3K/AKT signaling can increase accumulation of ROS in hCECs in vitro, indicating the vital role of PI3K/AKT signaling in ROS metabolism in corneal epithelium under the blue light exposure. Actually, many previous researches showed that blue light exposure can induce apoptosis of CECs in vivo and/or in vitro (2,24). And dysregulation of ROS stress is widely considered as an important mechanism of corneal epithelial damage caused by excessive blue light exposure(25-27).…”
Section: Discussionmentioning
confidence: 99%